2013
DOI: 10.1007/s10616-013-9665-0
|View full text |Cite
|
Sign up to set email alerts
|

Is there any genetic predisposition of MMP-9 gene C1562T and MTHFR gene C677T polymorphisms with essential hypertension?

Abstract: The current study was conducted to determine whether there is a relation between hypertension and two different polymorphisms, including C1562T of the Matrix metalloproteinase-9 (MMP-9) gene and C677T of the methylenetetrahydrofolate reductase (MTHFR) gene. Genomic DNA obtained from 224 persons (125 patients with hypertension and 99 healthy controls) were used in the study. Polymorphisms were determined by using polymerase chain reaction-restriction fragment length polymorphism and electrophoresis. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Generally consistent with these findings from genomewide association studies, there is a growing body of evidence from observational studies to support a specific association between the 677C T polymorphism in the MTHFR gene and BP variation (91)(92)(93)(94) . As the evidence has accumulated numerous meta-analysis were conducted, all reporting significant associations of the MTHFR 677C…”
Section: Novel Role Of Mthfr Genotype and Blood Pressuresupporting
confidence: 57%
“…Generally consistent with these findings from genomewide association studies, there is a growing body of evidence from observational studies to support a specific association between the 677C T polymorphism in the MTHFR gene and BP variation (91)(92)(93)(94) . As the evidence has accumulated numerous meta-analysis were conducted, all reporting significant associations of the MTHFR 677C…”
Section: Novel Role Of Mthfr Genotype and Blood Pressuresupporting
confidence: 57%
“…The results are well in line with other populations where, there was no significant difference in Northeastern Han Chinese and Turkish hypertensive subjects [15,24]. However, not in accordance with other studies done in isolated systolic hypertension among Han Chinese [33].…”
Section: C1562t and R279q Variants Of Mmp-9 Genesupporting
confidence: 78%
“…Several studies have been reported the association of lipid profiles in the hypertensive subjects with disagreeing results [15,33,34]. We evaluated association of clinical and biochemical characteristics with EH, which are tabulated in Table 3.…”
Section: Clinical and Biochemical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A numerous number of candidate genes and polymorphisms have been implicated in hypertension study as well as determinants risk factors (Agarwal, 2005). Recently, meta-analysis of wide genome association studies were done in large numbers of patients and identified various genetic loci linked not only with Blood Pressure (BP) variation (Levy et al, 2009;Newton-Cheh et al, 2009) but also in the individualization of the response to treatment (Bayramoglu et al, 2015;Fontana et al, 2015). Several studies reported the putative role of a mutation at nucleotide C677T in the methylenetetrahydrofolate reductase (MTHFR) gene (Xueqing et al, 2007).…”
mentioning
confidence: 99%